2018
DOI: 10.5152/tjg.2018.17707
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 10 and 14 days of triple therapy versus 10 days of sequential therapy for Helicobacter pylori eradication: A prospective randomized study

Abstract: Neither 10 d of ST nor 14 d of TT achieved the optimum H. pylori eradication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The average presenting age in our study was 40.0±24.4 years. This was similar to a local study in Lahore with 40.51±13.04 years and an international study in Qatar with 38.85±11.78 years [ 11 , 15 ]. Male predominance was seen in our study, which is consistent with a local study [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The average presenting age in our study was 40.0±24.4 years. This was similar to a local study in Lahore with 40.51±13.04 years and an international study in Qatar with 38.85±11.78 years [ 11 , 15 ]. Male predominance was seen in our study, which is consistent with a local study [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…Despite a large number of studies, the single best therapeutic regimen for the treatment of H. pylori could not be established. In trials, sequential therapy has shown higher eradication rates than standard triple therapy [ 11 , 12 ]. However, management guidelines differ among countries and depend on local susceptibility patterns [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the findings of this study present for the first time the cost-effectiveness of two commonly utilized H. pylori treatment regimens in Saudi Arabia. [ 15 16 17 18 ] The 10-day SQT was found to be more cost-effective than the 14-day STT with more than 50% level of confidence using probabilistic sensitivity analysis with 10,000 replications, that varied both H. pylori eradication rates, drug acquisition costs, and diagnostic procedures. These findings are consistent with previously published studies that showed SQT to be more cost-effective in eradicating H. pylori .…”
Section: Discussionmentioning
confidence: 99%
“…However, this difference in eradication rates between SQT and STT did not reach a statistically significant level in both intention to treat (ITT) and per protocol (PP) analyses. [ 15 ] Furthermore, in another single-center, randomized open-label trial that examined the efficacy of SQT versus STT in eradicating H. pylori in Saudi Arabia, the ITT eradication rates or treatment success rates as confirmed by the negative urea breath test (UBT) were 50.4% and 59% for SQT and STT, respectively; and, the PP eradication rates were 62.4% and 67.6% for SQT and STT, respectively. However, neither ITT nor PP eradication rates were significantly different between the two treatment regimens (i.e., SQT and STT).…”
Section: Introductionmentioning
confidence: 99%
“…Our sample consisted of a total of 7,829 patients, including both genders aged between 2 and 75 years. Studies from Egypt (n=18) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] , Saudi Arabia (n=8) [46][47][48][49][50][51][52][53] , Lebanon (n=6) [54][55][56][57][58][59] , UAE (n=5) [60][61][62][63][64] , Iraq (n=3) [65][66][67] , Qatar (n=3) [68][69][70] , Algeria (n=2) 71,72 , Palestine (n=1) 73 , Morocco (n=1) 74 , Syria (n=1) 75 , Yemen (n=1) 76 Tunisia (n=1) 77…”
Section: Patients and Study Characteristicsmentioning
confidence: 99%